Hubungan Kecerdasan Spiritual Terhadap Quarter Life Crisis Pada Mahasiswa - Kirana, Chevo Yusuf; Rini, Afinia Sandhya; Azfaruddin, Muhammad Farid (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The phenomenon of quarter life crisis is a reaction that arises from individuals to the emergence of anxiety about a life that is vacillating and unstable due to ongoing changes, many life choices, and also panic because they feel helpless. Becoming an adult is a must for every individual, which means that being an adult means being able to take responsibility for their actions, in addition to being able to fulfil their needs and contribute to society. For final year students, this crisis usually begins when individuals start to mess around with final assignments by writing papers or other substitute graduation requirements. graduation requirements in the form of other replacement tasks. The purpose of this study was to determine whether there is a correlation between spiritual intelligence and quarter-life crisis in final year students at Sayyid Ali Rahmatullah Tulungagung State Islamic University. This study uses a correlational quantitative approach. The population of this study were students who were in their final semester at Sayyid Ali Rahmatullah Tulungagung State Islamic University aged 23 to 25 years with a sample of 360 people. Data collection was carried out using a questionnaire and data analysis using Spearman's rho correlation analysis. The results showed a correlation value of -0.451 with a significance value of 0.000 (P < 0.05) so it can be concluded that there is a negative and significant correlation between the variable spiritual intelligence and quarter life crisis in final year students at Sayyid Ali Rahmatullah Tulungagung State Islamic University.